Changes in the Adsorption Properties of Activated Carbon due to Partial Oxidation of the Surface - A.M. Youssef; A.A. El-Khouly; A.I. Ahmed; E.I. El-Shafey (Adsorption Science & Technology)
The textural properties (surface area and porosity) of activated carbons change upon treatment with oxidizing solutions. The extent of this change is related to the strength of the oxidizing agent. Oxidation also changes the chemistry of the surface by forming carbon–oxygen groups which are the sites upon which the initial adsorption of water vapour takes place. The adsorption of water vapour at 300–320 K is mainly physical and the isosteric heat of adsorption decreases continuously as the surface coverage increases. The entropy of adsorption of water vapour on untreated and oxidized carbons, at different adsorption temperatures, has been calculated.